A Ricardian Analysis of the Impact of Climate Change on Latin American Farms - Seo, Niggol; Mendelsohn, Robert (World Bank, Washington, DC, 2012)
This study estimates the vulnerability of Latin American agriculture to climate change using a Ricardian analysis of both land values and net revenues. Examining a sample of over 2,500 farms in seven countries, the results indicate both land value and net revenue are sensitive to climate. Both small farms and large farms have a hill-shaped relationship with temperature. Estimating separate regressions for dryland and irrigated farms reveals that dryland farms are more sensitive to temperature but irrigated farms are more sensitive to precipitation. Examining the effects from future climate change scenarios reveals that severe scenarios could reduce farm earnings by as much as 62 percent by 2100, whereas more moderate scenarios could reduce earnings by about 15 percent. Small and large farms are equally sensitive to global warming. Land value and net revenue analyses produce quite similar results.